Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1038/s41467-017-02761-0
|View full text |Cite
|
Sign up to set email alerts
|

Ventromedial medulla inhibitory neuron inactivation induces REM sleep without atonia and REM sleep behavior disorder

Abstract: Despite decades of research, there is a persistent debate regarding the localization of GABA/glycine neurons responsible for hyperpolarizing somatic motoneurons during paradoxical (or REM) sleep (PS), resulting in the loss of muscle tone during this sleep state. Combining complementary neuroanatomical approaches in rats, we first show that these inhibitory neurons are localized within the ventromedial medulla (vmM) rather than within the spinal cord. We then demonstrate their functional role in PS expression t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 46 publications
(68 reference statements)
5
62
0
Order By: Relevance
“…Recent studies in mice and rats demonstrated the major role of inhibitory GABA/glycinergic synapses in motor pathways of the brainstem. Genetic inactivation in GABA/glycine neurotransmission in the ventromedial medulla disrupts muscle atonia during REM sleep and triggers abnormal behaviors without any effect during waking and slow‐wave sleep . Transgenic mice with deficient glycine and GABA‐A receptor function exhibited increased motor activity during NREM and REM sleep, NREM myoclonic jerks, sleep fragmentation, and increased phasic but normal tonic motor activities in REM sleep .…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Recent studies in mice and rats demonstrated the major role of inhibitory GABA/glycinergic synapses in motor pathways of the brainstem. Genetic inactivation in GABA/glycine neurotransmission in the ventromedial medulla disrupts muscle atonia during REM sleep and triggers abnormal behaviors without any effect during waking and slow‐wave sleep . Transgenic mice with deficient glycine and GABA‐A receptor function exhibited increased motor activity during NREM and REM sleep, NREM myoclonic jerks, sleep fragmentation, and increased phasic but normal tonic motor activities in REM sleep .…”
Section: Discussionsupporting
confidence: 67%
“…These mice also presented myoclonic jerks during non‐REM (NREM) sleep and large sleep fragmentation. Another model of RBD was recently reported in rats after selective inactivation of the GABA/glycinergic transmission in the ventral medial medulla . The precise role of impaired GABA/glycine transmission in the pathophysiology of human RBD remains unknown …”
Section: Introductionmentioning
confidence: 99%
“…A proportion of RSNs descending in the MLF are inhibitory (Du Beau et al, 2012 ), and approximately 20% of RS synaptic contacts on propriospinal and spinal commissural interneurons in the lumbar spinal cord are inhibitory (Mitchell et al, 2016 ). Recently it has been shown that glycinergic neurons located in the GRN descend to the lumbar spinal cord (Valencia Garcia et al, 2018 ; vide infra ).…”
Section: Reticulospinal Neurons Are Command Neurons For Movementmentioning
confidence: 99%
“…Both of these targets contribute to sleep atonia, but whether the direct descending command from the GRN is inhibitory and/or whether its inhibitory effects are mediated by spinal interneurons is not clear (Fuller et al, 2007 ; Arrigoni et al, 2016 ). Recent evidence, however, suggests that there is descending inhibitory input that produces sleep atonia (Valencia Garcia et al, 2018 ).…”
Section: Reticulospinal Neurons Are Command Neurons For Movementmentioning
confidence: 99%
“…In autopsy brains of PD patients who developed PD and dementia with Lewy bodies (DLB) preceded by idiopathic RBD, LBs were identified in the pedunculopontine tegmental nucleus (PPN), locus coeruleus/subcoeruleus complex, and gigantocellular reticular nucleus in medulla oblongata [46]. These regions are considered part of the neural circuit controlling atonia during REM sleep in animal experiments [6,47,48] and thus responsible for RBD. In this way the pathological progression of PD largely follows Braak's staging.…”
Section: Prodromal Symptoms Of Pd Patientsmentioning
confidence: 99%